Menyibak Masa Lalu, Menggapai Masa Depan Pasar Modal Indonesia Menuju Milenium III - Nindyo Pramono (Jurnal Hukum IUS QUIA IUSTUM, 2004)
Entering global era nowadays, Money Market should be directed to be competitive and it must be efficient in its management. Becoming an established Money Market in'the competition .and has high efficient in its management, the nextfive years the development ofIndonesia Money Market is focused in-developing the infrastructure and Money Market The Objectives are restructuring stock exchange, LPK and^LPP in im'provirig efficiency and the power on competition of Indonesia Money Market and ascertainingLPK stockexchange and certainly LPP is ready to face the dynamic marketchanges.